A tipologia jusfundamental positivada na Constituição de 1988: sistematização dos critérios de classificação e intangibilidade ao poder constituinte derivado - Santana, Fabrício de Oliveira (2011)
The present essay investigates the jusfundamental typology positivism in the Brazilian Constitution of 1988, analyzing its character and its scientific suitability classification, the systematic searching of its criteria, particularly the verification of the reaching of the inviolability of the fundamental rights derived as the constituent power of reforming the Constitution.